Civics and citizenship : theoretical models and experiences in Latin America - García-Cabrero, Benilde; Sandoval-Hernández, Andrés; Treviño, Ernesto; Ferráns, Silvia Diazgranados; Martínez, María Guadalupe Pérez (Moral development and citizenship education., 2017)
The book is organized around four sections. The first section is an introduction to the problem of defining the scope and foundations of the development of moral personality and social engagement, in particular, the development of civic and ethical attitudes and prosocial behavior. The second section presents a comparative analysis of education policies in Mexico, Chile and Colombia, in particular the way the curricula of civic and citizenship education is designed and implemented. The section also describes and analyzes the way this subject is taught in the classrooms of the primary, secondary and high school levels in the three countries. The third section includes the results of research projects in Civics and Citizenship Education conducted with different theoretical and methodological models of analysis. This last section includes some of the best practices of Civic Education that have been developed in Mexico, Colombia, and Chile.